Arhinia and Bilateral Anophthalmia - Mehrdad Jafari (Tehran University of Medical Sciences, 2021)
Arhinia is an extremely rare condition reported in less than 100 cases so far. We report a case of arhinia with bilateral anophthalmia. In physical examination, only alar portions of the nose were partially formed. No septal, lower, upper lateral cartilages or nasal bones were detectable. Both nostrils were atretic. The orbital area was covered with skin and eyebrows were partially formed. Bilateral complete cleft lip and palate was evident. Surgical interventions should be considered not only for reconstruction of the external nose, but for timely creation of a lacrimal passage and repair of the accompanying cleft lip and palate.